Answer:
The equation of the tangent line
![y - (\pi )/(4) = ((-\pi )/(2) +1)( x - (\pi )/(4) )](https://img.qammunity.org/2021/formulas/mathematics/college/n5u9rqxqev7io9cvcvsjdiyjxnqusbq0s6.png)
Explanation:
Step(i):-
Given function y = x cot (x) ....(i)
Differentiating equation (i) with respective to 'x' , we get
![(dy)/(dx) = x (-Co sec^(2) (x)) +cot(x) (1)](https://img.qammunity.org/2021/formulas/mathematics/college/lr4irwg0b4nk44hzpplviqn1rfhazhoyvp.png)
Step(ii):-
The slope of the tangent line
![(d y)/(d x) = -x Co-sec^(2) (x) +cot x](https://img.qammunity.org/2021/formulas/mathematics/college/dhyd80sl5qkfzgdl9cghj49rnjqt2a5m72.png)
![((d y)/(d x) )x_{=(\pi )/(4) } = -(\pi )/(4) Co-sec^(2) ((\pi )/(4) ) +cot (\pi )/(4)](https://img.qammunity.org/2021/formulas/mathematics/college/94hm7g44c90xxd15mdze8l71dwk8pszo4m.png)
We will use trigonometry formulas
![Cosec((\pi )/(4) ) = √(2)](https://img.qammunity.org/2021/formulas/mathematics/college/ryjcwl8swhjzkljd1803b0mb59za14k13t.png)
![sec((\pi )/(4) ) = √(2)](https://img.qammunity.org/2021/formulas/mathematics/college/e07x6hii8607f16rchmh0nk09zd1ir1mrd.png)
![Cot((\pi )/(4) ) = 1](https://img.qammunity.org/2021/formulas/mathematics/college/vaenqv1beh0el7ygzicjxjqhyfhxsoz8dm.png)
Now the slope of the tangent
![(dy)/(dx) =-(\pi )/(4) (√(2))^(2) )+1](https://img.qammunity.org/2021/formulas/mathematics/college/boerwq1am32gxunt7l0qm6ieq667zh9gkz.png)
![(dy)/(dx) =-(\pi )/(2) +1](https://img.qammunity.org/2021/formulas/mathematics/college/btsf2hv4thot5i7inw54l47gf939gzvxe1.png)
Step(iii):-
Given
Substitute
in y = x cot (x)
![y = (\pi )/(4) cot ((\pi )/(4) )](https://img.qammunity.org/2021/formulas/mathematics/college/zaz9du49eriine9brd1d3q5jg33k0u3nxe.png)
![y = (\pi )/(4)](https://img.qammunity.org/2021/formulas/mathematics/college/13ofpbyqrzxqwo52rq1u1hs8k69ebr6vcs.png)
The point of the tangent line
![(x ,y ) = ((\pi )/(4) , (\pi )/(4) )](https://img.qammunity.org/2021/formulas/mathematics/college/a026tz33l8ajlqjq1ruml7f8w3ioobu2fo.png)
The equation of the tangent line
![y - y_(1) = m ( x - x_(1) )](https://img.qammunity.org/2021/formulas/mathematics/middle-school/y9zg6lfw08w6i3fnrs3wgnms3t1dc7mlx0.png)
![y - (\pi )/(4) = ((-\pi )/(2) +1)( x - (\pi )/(4) )](https://img.qammunity.org/2021/formulas/mathematics/college/n5u9rqxqev7io9cvcvsjdiyjxnqusbq0s6.png)